Intra-host analysis of hepaciviral glycoprotein evolution reveals signatures associated with viral persistence and clearance - Gömer, André Philipp; Brown, Richard J. P.; Pfänder, Stephanie; Deterding, Katja; Reuter, Gábor; Orton, Richard; Seitz, Stefan; Bock, C.-Thomas; Cavalleri, Jessika M. V.; Pietschmann, Thomas; Wedemeyer, Heiner; Steinmann, Eike; et al. (Virus evolution, 2022)
Abstract. Even 30 years after the discovery of the hepatitis C virus (HCV) in humans there is still no vaccine available. Reasons for this include the high muta